2015
DOI: 10.1037/a0037274
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about intentions: Counterexamples to reasons for actions.

Abstract: Four experiments tested the idea that people distinguish between biconditional, conditional, and enabling intention conditionals by thinking about counterexamples. The experiments examined intention conditionals that contain different types of reasons for actions, such as beliefs, goals, obligations, and social norms, based on a corpus of 48 intention conditionals established through an extensive materials test (n = 136). Experiment 1 (n = 19) showed that retrieved alternative reasons suppress the affirmation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 96 publications
(166 reference statements)
0
9
0
2
Order By: Relevance
“…Previous work has shown that people tend to think differently about the actions when they have knowledge about the reasons behind those actions. An important step towards understanding the actions of others is reasoning about their intentions (Juhos, Quelhas, & Byrne, 2015;Walsh & Byrne, 2007). Children aged 6 and 8 years were tested with a new task: the change of intentions task, which included scenarios where an actor has an initial reason (desire or obligation) for an action, which is subsequently changed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that people tend to think differently about the actions when they have knowledge about the reasons behind those actions. An important step towards understanding the actions of others is reasoning about their intentions (Juhos, Quelhas, & Byrne, 2015;Walsh & Byrne, 2007). Children aged 6 and 8 years were tested with a new task: the change of intentions task, which included scenarios where an actor has an initial reason (desire or obligation) for an action, which is subsequently changed.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs whether participants are explicitly told about additional or alternative conditions, or instead retrieve them from memory (e.g., Cummins, Lubart, Alksnis, & Rist, 1991; De Neys, Schaeken, & D’Ydewalle, 2002, 2003; Dieusseurt, Schaeken, Schroyens, & d’Ydewalle, 2000; Verschueren, Schaeken, & d'Ydewalle, 2005), whether they make a categorical judgment about what follows, or a judgment about their degree of certainty in the conclusion (e.g., Geiger & Oberauer, 2007; Markovits, Brisson, & de Chantal, 2015; Markovits, Brunet, & Lortie Forges, 2010), and whether the additional condition is presented as an enabler, for example, “if the sun shone the plants bloomed” or a disabler, for example, “if the sun did not shine the plants did not bloom” (e.g., Markovits et al, 2010; see also Markovits & Potvin, 2001). In many everyday situations, causal outcomes are over‐determined or depend on multiple joint causes (e.g., Kominsky, Phillips, Gerstenberg, Lagnado, & Knobe, 2015; Rehder, 2014; Strickland, Silver, & Keil, 2017), and suppression occurs not only for inferences about causal relations but also for relations based on intentions (e.g., Juhos, Quelhas, & Byrne, 2015), inducements (e.g., Couto, Quelhas, & Byrne, 2017), and polite discourse (e.g., Bonnefon & Hilton, 2002, 2004; Demeure, Bonnefon, & Raufaste, 2009; see also Chan & Chua, 1994). Despite the extensive research on the suppression effect, no studies have examined how it interacts with other beliefs, or with other reasoning effects, such as the counterfactual elevation effect, to which we now turn.…”
Section: Conditional Suppression and Counterfactual Elevationmentioning
confidence: 99%
“…The MMT explained these results by applying the concept of mental models, which are defined as iconic representations of the possibilities elicited by a piece of given information (Johnson-Laird, 1983, 2006, 2010a, 2010b. The MMT suggests that human reasoning proceeds by representing possibilities and testing counterexamples to evaluate consistency (Johnson-Laird & Byrne, 1991;Johnson-Laird, Khemlani, & Goodwin, 2015) and to distinguish between biconditionals, conditionals, and intention conditionals (Juhos, Quelhas, & Byrne, 2015). An extension of the MMT that covers the meaning, representation, and use of negation has been recently proposed by Khemlani et al (2012Khemlani et al ( , 2014.…”
Section: Introductionmentioning
confidence: 99%